LEAq – Laboratório de Entomologia Aquática “Prof. Claudio Gilberto Froehlich” and the task of facing the biodiversity knowledge deficits on Caddisflies (Trichoptera), Bahia, Brazil - Calor, Adolfo Ricardo; Pereira, Rafael; Queiroz, Larissa Laiane; Vilarino, Albane; de Azevedo, Carlos Coracy Dultra; Queiroz, Amanda; Burgos-Miranda, Manoel Joaquim; Cavalcante-Silva, Amanda; Oliveira-Silva, Marcos Vinícius; Lucca, Giann; Quinteiro, Fabio Batagini; Dias, Everton Santos; et al. (FapUNIFESP (SciELO), 2023)
Insects are fundamental to biodiversity conservation in almost all ecosystems, and their population decline, and extinction directly result from environmental impacts. These facts are aggravated by the lack of knowledge of insect biodiversity, the so-called biodiversity deficits, especially the Linnean and Wallacean shortfalls. In freshwater ecosystems, biodiversity loss is higher among aquatic insects, and caddisflies comprise one of the most vulnerable orders. In this way, research focusing on describing new caddisfly species and understanding their distribution ranges will increase knowledge of caddisfly biodiversity. In the past 14 years, the team from the Laboratório de Entomologia Aquática “Prof. Dr. Claudio Gilberto Froehlich” (LEAq, Universidade Federal da Bahia, Brazil) and collaborators have been addressing these issues, resulting in 55 described species of caddisflies. Taxa in other insect orders have also received attention and an additional 16 species have been described (eight mayflies, four stoneflies, four neuropteran spongillaflies, and antlions). Here, eight caddisfly species are described and illustrated (Atopsyche froehlichi sp. nov., Austrotinodes zeferina sp. nov., Cernotina kariri sp. nov., Neoathripsodes froehlichi sp. nov., Notalina claudiofroehlichi sp. nov., Oecetis marcus sp. nov., Phylloicus froehlichi sp. nov., and Polycentropus claudioi sp. nov.), five of them in honor of LEAq’s patron. In addition, new distributional data are presented for 10 known species. A checklist of the caddisfly fauna of Bahia state is also presented, with 138 species, around 75% and 30% of them recorded and described by the LEAq team, respectively. Currently, for caddisflies, Bahia is the fifth most species-rich state in Brazil, and the first in the Brazilian Northeast region.
Keywords: Aquatic insects; Brazilian Northeast region; Linnean shortfall; Neotropical region; Wallacean shortfall